"The stress is indescribable": self-reported health implications from child welfare supervisors. Issue 2 (3rd July 2019) - Griffiths, Austin; Harper, Whitney; Desrosiers, Patricia; Murphy, April; Royse, David
ABSTRACT: Using data from a state-wide survey of frontline supervisors from a state child welfare agency, this study qualitatively examined how stress from their positions may have affected their perceived health. With a response rate of 44%, 117 frontline supervisors participated and provided 240 comments describing health consequences in their physical health, mental health, work-life balance, and development of unhealthy habits or behaviors. Implications from this study are discussed in the context of workplace stress and employee turnover.